anonymous
  • anonymous
algebraic math problem If 5a - 2b = b + 1 = 9, What is the value of a? What i'v got so far is 5a -2b = b + 1 = 9 + 2b + 2b 5a = 3b + 1 = 9 - 1 - 1 5a = 3b = 8
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Am i doing this right?
Owlcoffee
  • Owlcoffee
This is an application of an axiom, which is also called "trasitive" property. The axiom states that if a number "a" is equal to another number "b" but at the same time "b" is equal to a number "c", then "a" is equal to "c": \[a=b=c\] then: \[a=c\] \[b=c\] That's a summarization of it, but hopefully you get the point. so fo the problem: \[5a-2b=b +1=9\] we can view "5a-2b" as "a", "b+1" as "b" and "9" as "c", and it resonates with the structure of the trasitive axiom, so we can apply it: \[5a-2b=9\] \[b+1=9\] So now you have two equations, where one is univarable, so take the second one, solve for "b" and replace it on the first equation.
anonymous
  • anonymous
Oh wow I did not know about that property, and sadly i have many to learn on this road however thanks so much! my work was: background as you taught me 5a -2b = a b+1 = b 9 = c meaning two equations i have now 5a-2b=9 and b+1=9 and then to solve i took the univariable as suggested and was easier b + 1 = 9 -1 -1 b = 8 therefore i used b to solve for the second equation 5a - 2b = 9 5a - 2(8) = 9 5a - 16 = 9 +16 +16 5a = 25 5a / 5 = 25 / 5 a = 5 Thank you once again :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Owlcoffee
  • Owlcoffee
Very well done!

Looking for something else?

Not the answer you are looking for? Search for more explanations.